WAYS OF FORMING THE INNOVATIVE CULTURE IN AN ENTERPRISE - SOBOLIEVA, TETIANA; NEZAMEDINOVA, TETIANA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the organizational culture of the enterprise as an important internal subsystem and a prerequisite for the effective implementation of its development goals. It is established that the current stage of socio-economic relations requires the intensification of innovation activities aimed at the development and implementation of innovations, both to meet the needs of consumers and to improve internal business processes. Since the innovative activity of the enterprise is largely derived from the type of organizational culture, an important task is to strengthen its innovative component. This involves the formulation and adherence to innovative values, the coverage of which should be reflected in the company's documents, the system of motivation, transparent communication mechanisms and decisions made by management. The development of the organization's values should include a component that recognizes innovation as a priority and an important task of the enterprise. Innovative values can be formulated in the following areas: employees; financial activities; customers and consumers; sustainable development of the organization. Conducting "innovative" holidays dedicated to the achievements in innovation, both individual employees and the entire organization, will help to "consolidate" innovative values and increase motivation. The same goal can be promoted by the development of the corporate image of the organization, style, emblem, elements of recognition among competitors, as well as the development of branded clothing for production workers. To intensify innovation, it is important for managers to understand their key role in disseminating and prioritizing innovation among the company's tasks, establishing contact with employees, effective delegation of tasks, setting standards of conduct in the organization, personnel policy, and system of material and non-material incentives.
Keywords: organizational culture; models of organizational culture; innovation culture; innovative values; innovations